Library and media roles in information hygiene and managing information - Chisita, Collence Takaingenhamo, 1965- (Advances in information quality and management (AIQM) book series., 2022)
"The book explores the concept of information hygiene from a myriad of angles including but not limited to digital archiving, records management, libraries and information science, production and publishing, media, politics of the COVID-19 pandemic and vaccinations, twenty-first century literacies and information management among others"--